Chemical process equipment : selection and design - Couper, James R. (Elsevier/Butterworth-Heinemann, 2012)
Chemical Process Equipment is a results-oriented reference for engineers who specify, design, maintain or run chemical and process plant. This book delivers information on the selection, sizing and operation of process equipment in a format that enables quick and accurate decision making on standard process and equipment choices, saving time, improving productivity, building understanding. Coverage emphasizes common real-world equipment design, rather than experimental or esoteric, and focuses on maximizing performance. Legacy reference for chemical and rel.